2016
DOI: 10.5812/aapm.39314
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Successful Spinal Needle Placement Between Crossed-Leg Sitting Position and Traditional Sitting Position in Patients Undergoing Urology Surgery

Abstract: BackgroundThe patient’s position during spinal anesthesia administration plays a major role in the success of spinal needle insertion into the subarachnoid space. The traditional sitting position (TSP) is the standard position for spinal anesthesia administration, but the success rate for spinal anesthesia administration in the TSP is still quite low. The crossed-leg sitting position (CLSP) is one of the alternative positions for the administration of spinal anesthesia, which can increase the degree of lumbar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The number of spinal needle-bone contacts was lower in the SP group, nonetheless ease of needle insertion or space identification was the same in both groups ( 4 ). Manggala et al, compared the Crossed-Leg Sitting Position (CLSP) with TSP in patients undergoing urologic surgery and concluded that there was no significant difference in success rate of needle placement between the 2 groups and they suggested that the CLSP can be used as an alternative sitting position for administration of spinal anesthesia ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The number of spinal needle-bone contacts was lower in the SP group, nonetheless ease of needle insertion or space identification was the same in both groups ( 4 ). Manggala et al, compared the Crossed-Leg Sitting Position (CLSP) with TSP in patients undergoing urologic surgery and concluded that there was no significant difference in success rate of needle placement between the 2 groups and they suggested that the CLSP can be used as an alternative sitting position for administration of spinal anesthesia ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only one study compared the success of spinal needle placement between the crossed-leg sitting position (CLSP) and the TSP. In their research, Manggala et al ( 15 ) kept the patients in the CLSP by hugging a pillow. They used neither an imaging technique nor a patient comfort score.…”
Section: Discussionmentioning
confidence: 99%
“…Poor positioning can result into multiple needle pricks and needle-to-bone contacts, thus increasing risk of backache, epidural hematoma, neural trauma and post-dural puncture headache (PDPH). [5][6][7][8] Lumbar spine curvature increases significantly in the last trimester of pregnancy, shifting center of gravity towards abdomen causing lumbar hyperlordosis. 9 Hyperlordosis produces vertebral space narrowing; while lumbar flexion is difficult to achieve in pregnant patients making median approach for spinal puncture very difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Each position has its own advantages. 5 TSP is the most commonly used position by the anesthetist, providing uninterrupted access to median area of vertebrae without being restricted by upper part of the table. 5 In pendant position propped underarms reduce vertical pressure (gravity) on the vertebrae, thus increasing intervertebral and inter-spinous distance and interlamina gap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation